Effect of Remineralization Pretreatments on Human Dentin Permeability and Bond Strength - Abu Hasna, Amjad [UNESP]; Martinho, Frederico Canato; Sellan, Pablo Lenin Benitez [UNESP]; Pampuri, Camila Reis [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Pucci, Cesar Rogério [UNESP] (Hindawi, 2023)
This study aimed to evaluate Nd:YAG laser, calcium phosphate, and adhesive system effect as different pretreatments in different protocols on dentin permeability (DP) and bond strength (BS). Fifty human dentin discs were used (4 mm in diameter and 1,5 mm in height). Specimens were divided into five groups (n = 10): (A): adhesive system (control); (AL): adhesive system + Nd:YAG laser; (LAL): Nd:YAG laser + adhesive system + Nd:YAG laser; (PAL): calcium phosphate-based dentin desensitizer TeethMate + adhesive system + Nd:YAG laser; and group (PLAL): Nd:YAG laser + calcium phosphate-based dentin desensitizer + adhesive system + Nd:YAG laser. All materials were used according to the manufacturers’ instructions. The specimens were submitted to artificial aging (5,000 thermal cycles and 12 × 104 mechanical cycles) then a bond test was performed. DP was measured using the split chamber model. Data were submitted to one-way analysis of variance (ANOVA), paired t-test, RM ANOVA, and Tukey test ( p < 0.05 ). All treatments were effective in DP reduction. For BS, the groups PAL and PLAL had improved BS with a statistically significant difference of the control group (A). Nd:Yag laser irradiation and calcium phosphate-based desensitizing agents significantly reduced DP, and the association between them could improve the BS on resin-human dentin interface.